Assets and domestic units: methodological challenges for longitudinal studies of poverty dynamics. Issue 1 (2nd January 2021) - Brockington, Dan; Coast, Ernestina; Mdee, Anna; Howland, Olivia; Randall, Sara
ABSTRACT: Tracking change in assets access and ownership in longitudinal research is difficult. Assets are rarely assigned to individuals. Their benefit and management are spread across domestic units which morph over time. We review the challenges of using assets to understand poverty dynamics, and tracking the domestic units that own and manage assets. Using case studies from longitudinal research we demonstrate that assets can afford useful insights into important change.